Transparent Government: Making Visible the Assemblages and Citizen Work - Smith, Karen Louise (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The idea that a government who informs their citizens can better engage their citizens in democratic life underlies various laws and information practices. In the Ontario context, the sharing of the Hansard records of legislative debates online (from 1981 to present), the enactment of a freedom of information (FOI) law (1990), and the creation of eGovernment websites (mid 1990s onwards), each demonstrate initiatives centred around government's sharing of information with citizens. However, if we expect a change in “who can do what” (Florini, 2007, p. 1), citizens' information practices also require attention. L’idée qu’un gouvernement qui informe les citoyens permet une plus grande participation citoyenne à la vie démocratique est sous-jacente à de nombreuses lois et pratiques informationnelles. Dans le contexte de l’Ontario, le partage en ligne du journal des débats législatifs (de 1981 à aujourd’hui), la mise en œuvre de la loi sur l’accès à l’information (1990) et la création des sites web de gouvernance en ligne (de la mi 1990 à nos jours), sont autant d’initiatives centrées sur la notion du gouvernement qui partage de l’information avec ses citoyens. Cependant, si nous nous attendons à un changement du « qui fait quoi » (Florini, 2007, p. 1), les pratiques informationnelles de citoyens nécessitent également notre attention.